A FORMAÇÃO CONTINUADA DOS PROFESSORES ATUANTES NA REDE ESTADUAL DE ENSINO DE MINAS GERAIS - Ana Paula Pereira Arantes; Álex Gomes da Silva; Naime Souza Silva; Tereza de Jesus Ferreira Scheide (Universidade do Oeste Paulista, 2010)
The objective of this article is to identify continued formation of the teachers operating in the public educational system of Minas Gerais State, more specifically those who teach in the cities of Iturama and Bonfinópolis. The research was developed in the qualitative boarding, using as procedure the study of case. The research proceedings that made possible the achievement of the intended objective were: the application of questionnaires and half-structuralized interviews. Operating teachers from the public education systems of Minas Gerais State had participated of the research. The teachers who were part of the research were chosen from Iturama and Bonfinópolis, both cities from Minas Gerais State. It was chosen to be part of the research a teacher of each school of both cities that corresponded to the following requirements: has been teaching in public state system for more than one year and has agreed to be part of the research. As results of our work we have notice that there is, on part of those who participated in the research, a belief that the teacher´s continued formation programs offered by the State Secretary of Education would bring "miraculous prescriptions" for the improvement of the teaching practice. It´s necessary to raise teachers awareness that the pedagogic practice will only be improved from the moment the teacher decodes what has been learned in the continued formation programs and applies the theory in practice according to its necessity and reality, that can be diagnosed through its teaching experience.